His needs, her needs : building an affair-proof marriage - Harley, Willard F. (Grand Rapids, Mich. : F.H. Revell, 1994)
Includes material on the role of "admiration, affection, an attractive spouse, conversation, domestic support, family commitment, financial support, honesty and openness, recreational companionship, sexual fulfillment" in marriage.
Includes bibliographical references.
Keywords: Marriage -- United States; Communication in marriage -- United States; Married people -- United States -- Psychology